PENGEMBANGAN E-MODUL AJAR BERBASIS ETNOSAINS TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V PADA PELAJARAN IPAS SD NEGERI 116 ALLU - Ibrahim; Wati, Ni'ma; Mubarak, M. Fadli; A. Arif, Tamran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Educational transformation in the Merdeka Curriculum era demands a holistic approach to learning, one of which is through the fusion of Natural and Social Sciences into IPAS. However, high cognitive demands often clash with the reality of conventional teaching materials that are sterile from the students' sociocultural context. This article is a Research and Development (R&D) study that designs an ethnoscience-based IPAS E-Module for fifth-grade students at SD Negeri 116 Allu, Maros Regency. By integrating Bugis-Makassar local wisdom such as the Mattojang tradition and Nennu-nennu culinary, this E-Module is intended as cognitive scaffolding to sharpen students' critical thinking skills according to Robert H. Ennis's indicators. The E-Module development follows the ADDIE model and projects the output of valid, practical, and effective interactive media in HTML5 format to facilitate the transition of students' reasoning from the concrete operational stage to the formal operational stage